Knowledge bloats, love builds: Paul on how we are (not) to know things - Rogan, Wil (Scottish journal of theology, 2025)
Paul's epistemology was famously mapped onto his eschatology by J. Louis Martyn, but it must be mapped also onto his ecclesiology. For Paul, knowing is bound always and indissolubly to living with others. To understand how Paul would have us know things, then, we must focus not on knowledge as such, but on epistemic practices in ecclesial communities. Whereas the Corinthians' use of wisdom and knowledge made for fragmentation and dissolution in the body of Christ (1 Cor 1-4; 8-10), Paul would have practices with knowledge instantiate communion and care for one another, as is proper for Christ's body. Integral to theological knowing is a sense of what and whom theology is for, a sense being critically explored in recent evaluations of theological education.